A New Approach to Approximate Solutions for Nonlinear Differential Equation - Safia Meftah (International Journal of Mathematics and Mathematical Sciences)
The question discussed in this study concerns one of the most helpful approximation methods, namely, the expansion of a solution of a differential equation in a series in powers of a small parameter. We used the Lindstedt-Poincaré perturbation method to construct a solution closer to uniformly valid asymptotic expansions for periodic solutions of second-order nonlinear differential equations.